2018
DOI: 10.1021/jacs.8b01742
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Promoter-Free Ethylene Methoxycarbonylation over Ru-Clusters/Ceria: The Catalysis of Interfacial Lewis Acid–Base Pair

Abstract: The interface of metal-oxide plays pivotal roles in catalytic reactions, but its catalytic function is still not clear. In this study, we report the high activity of nanostructured Ru/ceria (Ru-clusters/ceria) in the ethylene methoxycarbonylation (EMC) reaction in the absence of acid promoter. The catalyst offers 92% yield of MP with TOF of 8666 h, which is about 2.5 times of homogeneous Pd catalyst (∼3500 h). The interfacial Lewis acid-base pair [Ru-O-Ce-Vö], which consists of acidic Ce-Vö (oxygen vacancy) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
121
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(134 citation statements)
references
References 108 publications
10
121
2
1
Order By: Relevance
“…Pt−O−Ce bond can be therefore generated on the interfaces between CeO x and Pt. Pt−O−Ce bond was observed at 71.9 eV clarified by Mori et al ., which was also similar to the reported Ru‐O−Ce bond . Pt−O−Ce bonds in C/PBI/Pt@CeO x were supposed to be formed during the hydrothermal process, agreeing well with previous report .…”
Section: Resultssupporting
confidence: 92%
“…Pt−O−Ce bond can be therefore generated on the interfaces between CeO x and Pt. Pt−O−Ce bond was observed at 71.9 eV clarified by Mori et al ., which was also similar to the reported Ru‐O−Ce bond . Pt−O−Ce bonds in C/PBI/Pt@CeO x were supposed to be formed during the hydrothermal process, agreeing well with previous report .…”
Section: Resultssupporting
confidence: 92%
“…1635 cm À 1 appeared in the spectrum of Nb 2 O 5 À L, which can be assigned to the coordination of carbonyl group of CPO with Lacid sites. [17] In the case of 1 %Ru/Nb 2 O 5 À L, the broad peak at around 1635 cm À 1 still exists, suggesting that CPO is indeed adsorbed on the support. However, two new peaks at 1592 cm À 1 and 1558 cm À 1 appear in the spectrum of 1 %Ru/ Nb 2 O 5 À L. The former one can be assigned to the carbonyl group in CPO adsorbed on the surface of Ru particles, and the latter one can be considered as the carbonyl group of the aldol condensed by-products (Figure 5a, others) coordinated to Lacid sites.…”
Section: Resultsmentioning
confidence: 92%
“…It can be seen only one broad band at ca. 1635 cm −1 appeared in the spectrum of Nb 2 O 5 −L, which can be assigned to the coordination of carbonyl group of CPO with L‐acid sites . In the case of 1 %Ru/Nb 2 O 5 −L, the broad peak at around 1635 cm −1 still exists, suggesting that CPO is indeed adsorbed on the support.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In ap revious study,w e reported the excellent catalytic performance of Ru-clusters/ ceria in the carbonylation of ethylene to methyl propionate. [15] Thus,the Ru-clusters/ceria was also applied in the synthesis of quinazolinones from olefins,C O, and amines.T he results showed that the reaction could proceed smoothly with a38% yield (by GC) of product 3.The yield increased to more than Scheme 1. Different catalytic systems for the synthesis of quinazolinones.…”
mentioning
confidence: 99%